(untitled) (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2021)
The pandemic has made learning at all levels of education that used to be face-to-face to be online or online. No exception at the level of basic education which requires every child to use a device. But not a few we meet, in fact children play gadgets excessively. With this situation, one aspect of children’s skills is not optimal to be developed. There are so many ways or processes that can be done to improve children’s skills or creativity. By making or playing playdough from this flour, it can help improve the skills or creativity of children in basic education. Children are directly involved and play an active role in every process of making and forming playdough games from the flour. Children can understand, calculate and think how to make playdough dough fit and become a playdough game from flour that is not inferior to plasticine playdough. In addition to training skills and creativity, playdough activities from flour are expected to distract children from frequently holding a gadget or smartphone.